Restricted connectivity and population genetic fragility in a globally endangered Hammerhead Shark - Pinhal, Danillo [UNESP]; Domingues, Rodrigo R.; Bruels, Christine C.; Ferrette, Bruno L. S.; Gadig, Otto B. F. [UNESP]; Shivji, Mahmood S.; Martins, Cesar [UNESP] (Springer Nature, 2020)
Vagile, large-bodied marine organisms frequently have wide range dispersion but also dependence on coastal habitats for part of their life history. These characteristics may induce complex population genetic structure patterns, with resulting implications for the management of exploited populations. The scalloped hammerhead, Sphyrna lewini, is a cosmopolitan, migratory shark in tropical and warm temperate waters, inhabiting coastal bays during parturition and juvenile development, and the open ocean as adults. Here, we investigated the genetic connectivity and diversity of S. lewini in the western Atlantic using large sample coverage (N = 308), and data from whole mitochondrial control region (mtCR) sequences and ten nuclear microsatellite markers We detected significant population genetic structure with both mtCR and microsatellites markers (mtCR: ΦST = 0.60; p < 0.001; microsatellites: Dest 0.0794, p = 0.001, FST = 0.046, p < 0.05), and isolation by distance (mtCR r = 0.363, p = 0.009; microsatellites markers r = 0.638, p = 0.007). Migration and gene flow patterns were asymmetric and female reproductive philopatry is postulated to explain population subdivisions. The notable population differentiation at microsatellites markers indicates low-levels of male-mediated gene flow in the western Atlantic. The overall effective population size was estimated as 299 (215–412 CI), and there was no evidence of strong or recent bottleneck effects. Findings of at least three management units, moderate genetic diversity, and low effective population size in the context of current overfishing calls for intensive management aimed at short and long-term conservation for this endangered species in the western Atlantic Ocean.
Keywords: elasmobranch conservation; Endangered species; Genetic connectivity; Genetic diversity